Ten Years' Experience in Robotic-Assisted Thoracic Surgery for Early Stage Lung Cancer - Casiraghi, Monica; Galetta, Domenico; Borri, Alessandro; Tessitore, Adele; Romano, Rosalia; Diotti, Cristina; Brambilla, Daniela; Maisonneuve, Patrick; Spaggiari, Lorenzo (The Thoracic and Cardiovascular Surgeon, 2019)
Background This study analyzed the short- and long-term outcomes of robotic-assisted thoracic surgery (RATS) for early stage non-small cell lung cancer (NSCLC).Methods From November 2006 to December 2016, we performed 363 RATS procedures. This study retrospectively reviewed 339 patients who underwent RATS for clinical stages I (n = 318) or II (n = 21) NSCLC.Results Twenty-nine patients underwent segmentectomy, 307 lobectomy, and 3 pneumonectomy. Conversion occurred in 22 patients (6.5%): 15 (4.4%) due to technical issues, 4 (1.2%) for oncological reasons, and 3 (0.9%) for bleeding. The median number of N1 and N2 stations resected was 2 and 3, respectively, and the median number of N1 and N2 lymph nodes resected was 9 and 6, respectively. Median operative time was 192 minutes for lobectomy, 172 minutes for segmentectomy, and 275 minutes for pneumonectomy. Median length of hospital stay was 5 days (2–191). The most common postoperative complication was prolonged air leak (12.1%). Major complications occurred in eight patients (2.4%). The 30-day and 90-day operative mortality was 0% and 0.3%, respectively. Two and 5-year cancer-specific survival rate was 96.1% and 91.5%, respectively. Five-year survival rate was 96.2% for patients who underwent segmentectomy, and 89.1% for lobectomy. All three patients who underwent pneumonectomy were alive at 5 years with no disease.Conclusions Besides the well-known short-term outcomes showing very low morbidity and mortality rates, mediastinal lymph node dissection during RATS adequately assesses lymph node stations detecting occult lymph node metastasis and leading to excellent oncologic results. However, these results await longer follow-up studies.
Keywords: robotic surgery; non-small cell lung cancer; minimally invasive surgery